PENGEMBANGAN TUJUAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Saifullah, Saifullah; Adawiyah, Rabiatul; Salamah, Salamah (Berajah Journal, 2024)
This study aims to develop PAI curriculum objectives that are more relevant, contextual, and comprehensive. The research method used was a qualitative approach with data collection techniques through literature study, observation, and in-depth interviews with educational experts and practitioners. The data were analyzed descriptively and inferentially using thematic and statistical analysis. The results showed that the objectives of the PAI curriculum developed should include aspects of strengthening aqidah, deepening religious knowledge, practicing worship, forming noble morals, and developing life skills based on Islamic values. The principles used in the development of PAI curriculum objectives include the balance between spiritual and material aspects, contextuality, and relevance to the needs of the times. The development strategies applied include revitalizing the curriculum, improving the quality of teachers, strengthening partnerships with parents and communities, and utilizing technology in learning. The implication of this study is the production of PAI curriculum objectives that are more comprehensive, in line with the times, and able to answer global challenges. The PAI curriculum developed is expected to provide adequate provision for students in facing global challenges and become a generation that is faithful, knowledgeable, noble, and able to contribute positively to society.